Financial Performance on Firm Value with Corporate Social Responsibility Disclosure as Moderating Variable - Suci Rianti Putri Ridwan; Andika Pramukti; Muhammad Faisal AR Pelu; Muslim Muslim (Fakultas Ekonomi, Universitas Muslim Indonesia, 2023)
The purpose of this study was to determine the effect of financial performance on firm value with corporate social responsibility disclosure in manufacturing companies in the food & beverage industry sector listed on the Indonesian stock exchange. The dependent variable of this study uses financial performance proxied using (ROE) (ROA), and the independent variable of this study is firm value proxied using Tobins'Q. This study uses secondary data in the form of annual reports with the period 2019-2021 and a total sample of 15. The data was obtained from the Indonesia Stock Exchange (BEI). Data processing using the IBM SPSS 16 program. Financial performance projected by ROE shows the results that ROE has a significant positive effect on firm value. And financial performance projected with ROA shows the result that ROA has no significant effect on firm value. Corporate Social Responsibility disclosure cannot moderate ROE financial performance on firm value and Corporate Social Responsibility disclosure is able to moderate the relationship between ROA financial performance on firm value. Our research was only conducted on food and beverage companies listed on the IDX, further researchers should use other sectors that have more companies or even research can be conducted on all companies listed on the IDX.